Divergent synthesis of indole-fused polycycles via Rh(ii)-catalyzed intramolecular [3 + 2] cycloaddition and C–H functionalization of indolyltriazoles. Issue 11 (29th September 2015) - Zhang, Yong-Sheng; Tang, Xiang-Ying; Shi, Min
Abstract : Intramolecular formal [3 + 2] cycloaddition and C–H functionalization of N -sulfonyl triazoles with indoles have been developed to synthesize potential indole-fused polycycles. Abstract : Rh(ii )-catalyzed divergent synthesis of polycyclic indolines and azepino[4, 5- b ]indoles through intramolecular [3 + 2] cycloaddition and C–H functionalization of indoles with N -sulfonyl 1, 2, 3-triazoles is described. The reaction pathways are controlled by the substituent type of indole.